G458(P) Child safety week 2014: a questionnaire based survey exploring parental safety practices and the impact of a county–wide safety campaign. (27th April 2015) - Plumb, L; Cuellar, B; Sampson, C; Bennett, I
Abstract : Introduction: Unintentional childhood injury is a major public health problem associated with significant mortality. In Gloucestershire there have been several fatal accidents among children related to heavy furniture, blind–cords and nappy bags as well as potentially harmful practices such as co-sleeping. In recent years, UK injury prevention programmes have halved the number of childhood accidental deaths. There is evidence that community-based campaigns encourage positive behavioural change and can potentially reduce the number of injuries requiring medical attention. Our aim was to explore carer awareness of four specific hazards (nappy sacks, cord blinds, co-sleeping and heavy furniture) linked to paediatric deaths within the region through the use of questionnaires and a standardised educational poster display. Materials and methods: A standardised safety awareness poster board was designed using approved charity leaflets. Six-hundred poster packs were distributed to public centres in Gloucestershire. Additionally, a questionnaire was offered to carers of children attending the Children's centre of Gloucestershire Royal Hospital during Child Safety Week. It explored their current safety practices as well as thoughts on the usefulness and impact of the poster campaign. Results: We obtained 103 questionnaire responses over five days, 96% of which were from parents. Almost a quarter of respondents were unaware of accidental deaths relating to nappy sacks, although most (82%) kept sacks out of a child's reach. Of the 57 respondents who had cord blinds at home 26% did not attach safety devices. Despite prominent national campaigns deterring co-sleeping, 42% of all respondents had co-slept with their children when aged less than one year old. Two-thirds (67%) reported securing large furniture items in place within their home. Many parents were aware of the hazards highlighted (average 1–10 scale rating, 8.2), and found the campaign useful (average 1–10 scale rating, 7.3). In 50% of cases the potential to alter current practices perceived by carers was encouraging (average 1–10 scale rating, 5.3). Conclusion: A poster campaign highlighting hazards implicated in local deaths is deemed useful by parents. Further work through the use of focus groups and parental communication is required to identify how best to promote safety practices for future campaigns.